Abnormal ribosome assembly in a mutant of Escherichia coli. - Butler, P D (1979)
The mutant strain, 15--28, of Escherichia coli accumulates ribonucleoprotein ('47S') particles that were previously shown [Markey, Sims & Wild (1976) Biochem. J. 158, 451--456] to be an unusual intermediate in the assembly of 50S ribosomal subunits...